Doing thinking: revisiting computing with artistic research and technofeminism. Issue 4 (2nd October 2019) - Britton, Loren; Klumbyte, Goda; Draude, Claude
ABSTRACT: In this paper, we explore how artistic research and its methodologies can create new modes of thinking and research on computational issues. We draw on experiences with the research project 'Reconfiguring Computing Through Cyberfeminism and New Materialism' (CF+), during which we collaboratively investigated modes and methods of knowledge production in computing. Cyberfeminist legacies and new materialism provided a historically informed and theoretically rigorous set of concerns around which artistic research and computing were brought together. We discuss collaborative experiments and three hybrid methodologies – creating situations for intra-action, diffractive reading/making and material speculation – that we employed and suggest that what emerged is a kind of 'doing thinking' as a material-speculative practice that re-positions research as a critical open-ended space for non-standard ways of knowing. The paper explores implications of this for ethics and responsibility in computing, materiality of knowledge production and modes of interdisciplinary collaborations.